Is There a Threshold Concentration of Cat Allergen Exposure on Respiratory Symptoms in Adults? - Chen, Chih-Mei (PLoS One, 2015)
BACKGROUND AND OBJECTIVE: Cat allergen concentrations higher than 8 μg/g in settled house dust, have been suggested to provoke exacerbation of allergic respiratory symptoms. However, whether the 8μg/g of indoor cat allergen concentration is indeed the minimal exposure required for triggering the asthma related respiratory symptoms or the development of sensitization has not yet been confirmed. We studied the associations between domestic cat allergen concentrations and allergic symptoms in the European Community Respiratory Health Survey II, with the aim of confirming this suggested threshold. METHODS: Cat allergen concentrations were measured in the mattress dust of 3003 participants from 22 study centres. Levels of specific immunoglobulin E to cat allergens were measured in serum samples using an immunoassay. Information on allergic symptoms, medication use, home environment and smoking was obtained from a face-to-face interview. RESULTS: Domestic cat allergen concentrations were not associated with allergic/ asthmatic symptoms in the entire study population, nor in the subset sensitized to cat allergen. We also found no association among individuals exposed to concentrations higher than 8 μg/g. However, exposure to medium cat allergen concentrations (0.24-0.63 μg/g) was positively associated with reported asthmatic respiratory symptoms in subjects who have experienced allergic symptoms when near animals. CONCLUSIONS: The proposed 8 μg/g threshold of cat allergen concentrations for the exacerbation of allergic/ respiratory symptoms was not confirmed in a general European adult population. Potential biases attributable to avoidance behaviours and an imprecise exposure assessment cannot be excluded.